Adjusting to skill shortages: Complexity and consequences - Joshua Healy; Kostas Mavromaras; Peter J. Sloane (Institute for the Study of Labor (IZA), 2011)
Skill shortages are often portrayed as a major problem for the economies of many countries including the Australian economy. Yet, there is surprisingly little evidence about their prevalence, causes and consequences. This paper attempts to improve our understanding about these issues by using econometric methods to analyse the Business Longitudinal Database, an Australian panel data-set with information about skill shortages in small- and medium-sized businesses during 2004/05. We use this information to: (1) explore the incidence of skill shortages and the business attributes that are associated with them; (2) identify which businesses face more complex skill shortages, as measured by the number of different causes reported simultaneously; and, uniquely, (3) examine how this complexity affects businesses' responses to skill shortages and aspects of their subsequent performance. We show that complex skill shortages are more likely than simpler (single-cause) skill shortages to persist and to trigger defensive responses from businesses. We reject the conception of skill shortages as a homogenous phenomenon, and demonstrate the importance of distinguishing between skill shortages according to whether they have simple or complex causes.
urn:nbn:de:101:1-201111213253
Keywords: J0; J20; J23; J24; 330; skill shortages; small medium enterprises; Unterbeschäftigung; KMU; Qualifikationsbedarf; Australien